Teacher-student verbal communication and student learning - Hardi Yunius bin Kasim; Kayame de Joseph (International Journal of Curriculum Development, Teaching and Learning Innovation, 2022)
Teachers and students communicate through curiosity and attention. In social psychology, the instructor communicates and the pupil receives. Teaching-learning involves students getting teaching materials in various forms and teachers offering them in a dialogic style at a given time and location. Teacher-student contact is essential for effective teaching and learning. Teachers and students exchange psychological messages. Student learning achievement is multifaceted. Teachers' verbal communication skills affect student learning. Verbal communication—spoken or written—uses symbols or words. Teachers require solid language skills and a vast vocabulary to speak verbally because kids cannot understand specific words alone. This study seeks to understand how teacher verbal communication is implemented, how student learning is affected, and how. The association between verbal communication (variable X) and student learning success (variable Y) is researched using a quantitative descriptive method using a correlational study type, Product Moment (r). This strategy examines how components are connected.